Bisphenol A disrupts the temporal pattern of histofunctional changes in the female reproductive tract of Caiman latirostris - Galoppo, Germán Hugo (2017)
Recently, we have described the ontogeny of histofunctional differentiation changes in the oviduct of Caiman latirostris. The expression of estrogen receptor alpha and progesterone receptor shows that the caiman oviduct could be a target of the action of xenoestrogens such as the widely environmentally present Bisphenol A (BPA), early in life. The aims of this study were: to complement oviduct characterization by establishing the ontogenetic changes in androgen receptor (AR) expression and assessing the effects of early postnatal exposure to 17-β-estradiol (E2) or BPA on the histofunctional features of the oviduct. AR was expressed in all the stages studied. The spatial pattern of AR immunostaining changed from neonatal to juvenile caimans. In the luminal epithelium, changes were at the subcellular level, from cytoplasmic to nuclear. In the subepithelium, although both cytoplasmic and nuclear AR expression was observed, changes were mainly at tissue level, from the subepithelial compartment to the outer muscular layer. The oviduct was highly sensitive to E2 and BPA at the early postnatal developmental stage. E2- and BPA-exposed caimans showed increased luminal epithelial height and higher proliferative activity. Changes in histomorphological features (measured by a scoring system), steroid hormone receptors, collagen remodeling and muscle-associated proteins suggest a precocious oviduct histofunctional differentiation in E2- and BPA-exposed caimans. The modification of the temporal pattern of oviductal biomarkers suggests that organizational changes could impair C. latirostris reproductive health later in life. The alterations in the caiman female reproductive tract exposed to BPA highlight the importance of preserving aquatic environments from plastic pollution.